2020
DOI: 10.3934/dcds.2020202
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic behavior for a Schrödinger equation with nonlinear subcritical dissipation

Abstract: We study the time-asymptotic behavior of solutions of the Schrödinger equation with nonlinear dissipationWe give a precise description of the behavior of the solutions (including decay rates in L 2 and L ∞ , and asymptotic profile), for a class of arbitrarily large initial data, under the additional assumption that α is sufficiently close to 2 N .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…[9,12,27]). For the dissipative case Im λ < 0, there are several works that study the precise large time behavior when p ≤ 1 + 2/n (see [3,4,6,14]) and the exponent p = 1 + 2/n plays a critical role not for the scattering but the large time behavior. In recent work [5] (cf [16]), it is shown that there exists a scattering state…”
Section: Introdutionmentioning
confidence: 99%
“…[9,12,27]). For the dissipative case Im λ < 0, there are several works that study the precise large time behavior when p ≤ 1 + 2/n (see [3,4,6,14]) and the exponent p = 1 + 2/n plays a critical role not for the scattering but the large time behavior. In recent work [5] (cf [16]), it is shown that there exists a scattering state…”
Section: Introdutionmentioning
confidence: 99%
“…Recently Cazenave and Han established the long-time behavior for nonlinear autonomous Schrödinger equation in R n with a nonlinear subcritical dissipation [17].…”
Section: Introductionmentioning
confidence: 99%
“…and gave the characterizations of finite time blow up, boundedness and convergence to the ground state for the initial boundary value problem of Equation (5) with…”
mentioning
confidence: 99%
“…Lian and Xu [17] proved the asymptotic behavior for the nonlinear wave equation with weak and strong damping terms and logarithmic source term. Cazenave and Han [5] studied asymptotic behavior Schrödinger equation with nonlinear dissipation. For the fourth-order wave equation with strong damping, Yang et al [29] derived the existence of strong and weak uniform attractors with non-compact external forces.…”
mentioning
confidence: 99%